2020
DOI: 10.18632/oncotarget.27569
|View full text |Cite
|
Sign up to set email alerts
|

Lack of CD8+ T-cell co-localization with Kaposi’s sarcoma-associated herpesvirus infected cells in Kaposi’s sarcoma tumors

Abstract: Despite the close association between Kaposi's sarcoma (KS) and immune dysfunction, it remains unclear whether tumor infiltrating immune cells (TIIC), by their absence, presence, or dysfunction, are mechanistically correlated with KS pathogenesis. Therefore, their potential capacity to serve as prognostic biomarkers of KS disease progression or control is unclear. Because epidemic-KS (EpKS) occurs with HIV-1 co-infection, it is particularly important to compare TIIC between EpKS and HIV-negative African endemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 53 publications
7
17
0
Order By: Relevance
“…Previous report showed that TGF-β suppresses CD8+ effector T-cell function, inhibits the Th1 phenotype, and activates M2 macrophages polarization, driving immune cells from the tumor compartment [ 45 ]. We found that the CD8 T cell fraction was negatively associated with M0 and M2 macrophages, and positively associated with M1 macrophages in sarcomas samples, consistent with the previous reports [ 46 , 47 ], suggesting that CD8 T cells and macrophages may be potential markers for the prognosis of patients with sarcoma.…”
Section: Discussionsupporting
confidence: 92%
“…Previous report showed that TGF-β suppresses CD8+ effector T-cell function, inhibits the Th1 phenotype, and activates M2 macrophages polarization, driving immune cells from the tumor compartment [ 45 ]. We found that the CD8 T cell fraction was negatively associated with M0 and M2 macrophages, and positively associated with M1 macrophages in sarcomas samples, consistent with the previous reports [ 46 , 47 ], suggesting that CD8 T cells and macrophages may be potential markers for the prognosis of patients with sarcoma.…”
Section: Discussionsupporting
confidence: 92%
“…Previous report showed that TGF-β suppresses CD8+ effector Tcell function, inhibits the Th1 phenotype, and activates M2 macrophages polarization, driving immune cells from the tumor compartment [45]. We found that the CD8 T cell fraction was negatively associated with M0 and M2 macrophages, and positively associated with M1 macrophages in sarcomas samples, consistent with the previous reports [46,47], suggesting that CD8 T cells and macrophages may be potential markers for the prognosis of patients with sarcoma.…”
Section: Discussionsupporting
confidence: 91%
“…In HIV-associated KS patients, neutrophil function has been reported to be compromised [ 27 ]. This is supported by a recent study on tumor infiltrating immune cells in KS tumors, which did not observe any neutrophil infiltration in KS tumor biopsies [ 28 ]. Therefore, the KS tumor environment and associated cytokines which are elevated in KS patients, such as IL-6, may also contribute towards KS immune evasion through the neutrophil pathway.…”
Section: Cells Of Innate Immunity In Kshv Infection and Kssupporting
confidence: 78%
“…In one study, it was observed that KSHV-specific CTLs were not recruited to KS lesions in KSHV-infected individuals who progressed to KS [ 78 ]. This is supported by a more recent study that observed and reported statistically significant sparse distribution of CD8 + T cells in regions of KS tumor biopsies with evident KSHV-infected cells compared to regions of KS tumor biopsies that were devoid of KSHV infection which had readily detectable CD8 + T cells [ 28 ].…”
Section: Adaptive Responses In Kshv Infection and Kssupporting
confidence: 61%
See 1 more Smart Citation